Distribuição Espacial e Temporal do Macrozoobentos de Habitats Entremarés do Canal da Raposa, Baía de São Marcos, Maranhão, Brasil - COSTA, Clarissa Moreira Coelho (2017)
Macrozoobenthos of different grain size intertidal habitats were sampled during wet and dry seasons on Raposa Channel, Maranhão State, Brazil. The sampling was made with a PVC corer. The benthic organisms was sieved using 1 and 0,5 mm sieves and identified under a stereoscopic microscope. There were a few dominant species despite of many rare ones. Paraonis agilis, Notomastus aberans, Capitella capitata and Odontosyllis heterofalchaeta had high densities on Raposa Channel habitats. The macrozoobenthos had higher densities during wet season, specially the deposit and suspension feeders. The deposit feeders were dominant at higher silt/clay content habitats, while the suspension feeders dominated higher sand content ones. These habitats were the most diverse. Ceratia rustica, Vitrinella filifera, Paraonis agilis, Scaphopoda indet. and Caecum sp had high contribution on dissimilarity between habitats, most expressive during dry season. Sediment humidity, organic mater content, sand, silt and clay percentages and grain selection showed that habitats were significantly differents.